PENGARUH PEMBIAYAAN USAHA MIKRO KECIL MENENGAH (UMKM) TERHADAP LABA OPERASIONAL PADA PT. BRI SYARIAH CABANG MEDAN - Sahputra, Ngatno (Jurnal Ilmiah Al-Hadi, 2018)
PT. BRI Syariah as a State-Owned Enterprise in the field of financial institutions, which owns the product of fund raising and fund distribution in the form of financing including the financing of Micro Small Medium Enterprises (UMKM). This study aims to determine and analyze the Influence of Micro Small Medium Business Financing (UMKM) Against Operating Profit At PT. BRI Syariah Branch Medan. Data collection techniques researchers do with field research (field research) is research directly to the company that became the object of research that aims to obtain the required data in connection with the material discussion. Data for the last 4 years, namely: (2011 - 2014) representing the population in this study. The method used is simple linear regression. The results showed that the financing can affect the profit, it is evident from the value of Fhitung shows the value of 133.097 and ftable obtained by 4.130 meaning is that the independent variable of UMKM financing together influence on the dependent variable that is operational profit. Based on the proposed hypothesis, the discussion obtained is the variable channeling of UMKM (X) has a positive and partially significant effect on the variable operating profit (Y).